An unusual case of long standing vaginal foreign body removed with obstetric forceps - ., Padmalata; Fathima, Naima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
This is a case of retained foreign body in vagina for 10 years, a wood apple which was inserted to reduce uterine prolapse. It was retained without any symptoms for 10 years. The foreign body was removed using obstetric forceps after other methods were failed.